Pernilaian Teknologi 2 Industri Pembuat Skop Dengan Metode Teknometrik - Retno Indriartiningtias; Resta Amijaya; Widi Nugroho (Jurnal METRIS, 2014)
Technology is one of the factors affecting the competitiveness of small industries. The higher the mastery of a small industrial technology can dominate the market. Technology here is not only physical facilities but also non-physical facilities such as a human, information and organization. UD Dua Udang and UD Naga Timur are SMEs engaged in the production of household appliances, one of which scop shoes. UD Naga Timur is on eof leader SME his business and includes one of the SMEs which have a market share larger than similar SMEs. UD Dua Udang is a newly established SMEs. This study discusses the performance evaluation technology of the two SMEs. The results of the assessment could use by UD Dua Naga to devise a strategy in order to compete with UD Naga Timur. Methods for assessing the performance of technology used was technometric (Technoware, Humanware, Infoware and Orgaware). From the research results that are both at the level of traditional technologies. UD Naga Timur got higher values for Infoware and Orgaware. UD Dua Udang should fix both of these components by improving the documentation system and also expanding its network by entering its products at a wholesale market in Surabaya and surrounding areas.